LANGUAGE AND IDENTITY: HOW DIALECTS SHAPE CULTURAL BELONGING - Xojabekova , Ramzida (Scientific practical conference, 2026)
This article examines the relationship between language, dialects, and cultural identity, focusing on how dialectal variation shapes a sense of belonging within communities. It explores the sociolinguistic role of dialects as markers of regional, social, and cultural identity, emphasizing their importance in preserving cultural heritage and collective memory. The study also discusses the social perceptions associated with dialects, including issues of prestige, stigma, and linguistic discrimination. Furthermore, the article analyzes the impact of globalization, digital communication, and education on dialect usage and attitudes toward linguistic diversity. The research concludes that dialects remain vital instruments of cultural expression and identity formation, highlighting the need to recognize and preserve dialect diversity in modern society.